Pembuatan Streetwear Kombinasi Batik Dengan Teknik Hias Origami - Romdhona Chusna Tsani; Novita Anggraini (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2023)
Streetwear is street clothing that is used every day and can be combined with various clothes that create a relaxed yet attractive effect. Batik, the fabric that is characteristic of Indonesia, is also widely combined with various models of clothing. Origami combination that would be applied to the fabric aimed to create decorative techniques so that the clothes are unique and interesting. The aim of this study was to determine how is the process of making batik streetwear with origami decorative techniques. The research method used was qualitative. The data collection methods used was literature, observation and documentation. The combination of origami placed on the shirt and outer sleeves produced a different artistic value, with the composition that has been considered so that they will look harmonious when wearing origami and batik. The production of this dress used the basic pattern of the Soen system so as to obtain pieces of clothing, darts, sleeves and sizes that are comfortable when worn. The conclusion of making streetwear that has been done was the cutting process of batik and materials must be done correctly. Then, pressing was also important to obtain good origami results.The suggestions for the next opportunity in making origami was on the arms should use layers to obtain arms that have firmness. The manufacture of streetwear clothing with a combination of origami should pay more attention to the materials used and the pressing process.